Characterization of hospitalizations for childhood leukemia in a Brazilian capital (Research, Society and Development, 2022)
Introduction: Leukemia is the most common type of cancer in childhood. Among the types of childhood leukemia, acute myeloid and acute lymphoblastic leukemia prevail. Survival has been showing a significant improvement. Patients need several hospital admissions for chemotherapy and treatment of complications. Objective: To analyze hospitalizations for childhood leukemia in a Brazilian capital, 2010 to 2020. Methodology: This is a descriptive and retrospective cross-sectional epidemiological study, with secondary data from the Hospital Admission Authorization (AIH) - Hospital Information System of the Department of Informatics of the Unified Health System of the Ministry of Health. Descriptive statistical analysis was conducted and the results presented in absolute and relative frequency. Results: From 2010 to 2020, there were 425 hospitalizations of patients (under 14 years old) diagnosed with childhood leukemia, an average of 39 hospitalizations per year, and an increasing trend in the period, 2019 and 2020 with more hospitalizations, 69 (16%) and 62 (14 %), respectively. There was a predominance of male hospitalizations (62%), age group from 1 to 5 years old (47%), and mixed race (69.0%). Acute lymphoblastic leukemia (81%) was prevalent. The most performed procedure was the administration of chemotherapy (50%). In the period, 13 patients died during hospitalization. Conclusion: This information can provide evidence for decision-making and the implementation of public health policies, aimed at the diagnosis and treatment of childhood leukemia.